2015
DOI: 10.1002/pc.23803
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the fracture toughness of glass fiber reinforced polyamide 6,6 composites with the addition of chain extender

Abstract: The aim of this study is to improve the fracture toughness of glass fiber reinforced polyamide 6,6 (PA6,6) composites by adding 1,4-phenylene-bis-oxazoline (PBO). Essential work of fracture (EWF) analysis was conducted to analyze the effect of chain extender loading level on the fractural properties of composites. Three different wt% levels of chain extender were used (0.5, 1.0, and 2.0 wt%). Results of EWF analysis revealed that 1.0 wt% PBO addition made a great contribution to the fracture energy of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The 12 mm FL and the resin skin on the fiber surface would result in effective stress transfer between the resin and 12 mm FL under applied stresses. [27][28][29] Furthermore, there is a significant improvement in fiber/resin adhesion, as seen by the absence of voids and debonding. Also, most of the fibers with 12 mm FL had a more particular and regular orientation than those with 3 mm FL in the specimens.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…The 12 mm FL and the resin skin on the fiber surface would result in effective stress transfer between the resin and 12 mm FL under applied stresses. [27][28][29] Furthermore, there is a significant improvement in fiber/resin adhesion, as seen by the absence of voids and debonding. Also, most of the fibers with 12 mm FL had a more particular and regular orientation than those with 3 mm FL in the specimens.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…The significant advantages of EWF over J-integral are simplicity of testing, simple preparation, ability to measure failure behavior not only until the crack start but also during the crack propagation period. [29][30][31] The EWF methodology has been used by many researchers to investigate the fracture properties of blend nanocomposites. Haghnegahdar et al [32] indicated that the addition of multi-layer graphene (MLG) and fewlayer graphene (FLG) to the PP/EPDM had a different trend in the EWF but increased the non-EWF for both types.…”
Section: Introductionmentioning
confidence: 99%
“…The significant advantages of EWF over J‐integral are simplicity of testing, simple preparation, ability to measure failure behavior not only until the crack start but also during the crack propagation period. [ 29–31 ]…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37] In addition, Amino-silicate is used as a chain extender to improve the interfacial adhesion between glass fiber and the PA612 matrix. 38 It is known from the literature that GFreinforced PA612-based composites are applied in many applications as key components requiring wear resistance, such as journal bearings, gears, cams, and rolling bearings. 21 This case is because, during the sliding process, the PA612 composite material can form a uniform and thin transfer film.…”
Section: Introductionmentioning
confidence: 99%